Protein-RNA linkage and posttranslational modifications of feline calicivirus and murine norovirus VPg proteins - Allan Olspert; Myra Hosmillo; Yasmin Chaudhry; Lauri Peil; Erkki Truve; Ian Goodfellow (PeerJ, 2016)
Members of the Caliciviridae family of positive sense RNA viruses cause a wide range of diseases in both humans and animals. The detailed characterization of the calicivirus life cycle had been hampered due to the lack of robust cell culture systems and experimental tools for many of the members of the family. However, a number of caliciviruses replicate efficiently in cell culture and have robust reverse genetics systems available, most notably feline calicivirus (FCV) and murine norovirus (MNV). These are therefore widely used as representative members with which to examine the mechanistic details of calicivirus genome translation and replication. The replication of the calicivirus RNA genome occurs via a double-stranded RNA intermediate that is then used as a template for the production of new positive sense viral RNA, which is covalently linked to the virus-encoded protein VPg. The covalent linkage to VPg occurs during genome replication via the nucleotidylylation activity of the viral RNA-dependent RNA polymerase. Using FCV and MNV, we used mass spectrometry-based approach to identify the specific amino acid linked to the 5′ end of the viral nucleic acid. We observed that both VPg proteins are covalently linked to guanosine diphosphate (GDP) moieties via tyrosine positions 24 and 26 for FCV and MNV respectively. These data fit with previous observations indicating that mutations introduced into these specific amino acids are deleterious for viral replication and fail to produce infectious virus. In addition, we also detected serine phosphorylation sites within the FCV VPg protein with positions 80 and 107 found consistently phosphorylated on VPg-linked viral RNA isolated from infected cells. This work provides the first direct experimental characterization of the linkage of infectious calicivirus viral RNA to the VPg protein and highlights that post-translational modifications of VPg may also occur during the viral life cycle.